Budget inflexibility (2005)
The study of budgetary institutions has long been an important topic in the economic literature. Nonetheless, the degree of rigidity or inflexibility in budget preparation, a prime preoccupation for policy makers and in particular for finance ministers since a long time ago, has been relatively unexplored. In this paper we show that budget inflexibility can take several forms and argue that it is likely to be closely related to various types of political conflict present in the budget process. Moreover, we study one particular form of budget inflexibility and its connection with one specific (but perhaps the most important) political force driving the budget process. More specifically, we discuss some of the consequences of "expenditure inflexibility," defined as the existence of transfers to special interests enjoying constitutional or legal protection which impede their modification in the short run, in a simple model of legislative bargaining that captures the Tragedy of the Commons present in public budget allocation.